2022
DOI: 10.1038/s41598-022-13474-w
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long-term prognosis in rheumatoid arthritis-related interstitial lung disease

Abstract: The aim of the study was to identify specific clinical and serum protein biomarkers that are associated with longitudinal outcome of RA-associated interstitial lung disease (RA-ILD). 60 RA patients with clinical and serological profiles were assessed by HRCT and pulmonary function tests (PFTs) at baseline (Year 0) and 5 years post enrollment (Year 5). Progression versus non-progression was defined based on changes in Quantitative Modified HRCT scores and PFTs over time. Specific serum protein biomarkers were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
(53 reference statements)
1
7
0
2
Order By: Relevance
“…A recent systematic review and meta-analysis including 29 records concluded that both the presence and higher titers of ACPA were suggested to be significantly associated with an increased risk of RA-ILD [ 4 , 11 , 16 , 17 ]. Pursuant to that, our results were in line with literature data: ACPA positivity and rate were significantly higher in RA-ILD than in RA without ILD, and the absence of ACPA was a protective factor from RA-ILD (OR=0.294; p=0.03).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent systematic review and meta-analysis including 29 records concluded that both the presence and higher titers of ACPA were suggested to be significantly associated with an increased risk of RA-ILD [ 4 , 11 , 16 , 17 ]. Pursuant to that, our results were in line with literature data: ACPA positivity and rate were significantly higher in RA-ILD than in RA without ILD, and the absence of ACPA was a protective factor from RA-ILD (OR=0.294; p=0.03).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, selection criteria of 2 groups, especially in terms of disease duration, allowed to avoid confounded factors. Many studies had showed association between higher disease activity and ILD [ 4 , 12 , 21 , 22 ], however the study design must be reviewed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Частота клинически значимого ИЗЛ при РА колеблется от 6 до 15%, но по данным компьютерной томографии высокого разрешения (КТВР) признаки ИЗЛ обнаруживаются у 30-70% пациентов [18][19][20] и могут предшествовать клинической манифестации артрита [21][22][23][24]. Продолжительность жизни у пациентов с РА-ИЗЛ варьирует от 3 до 10 лет после постановки диагноза ИЗЛ [20], а риск летальности в 2-10 раз выше, чем при РА без ИЗЛ [25][26][27][28][29][30], превосходит этот показатель у пациентов РА с кардиоваскулярной патологией (отношение рисков (HR, hazard ratio) -7,98 и 4,10 соответственно) и соответствует риску летальности при идиопатическом легочном фиброзе (ИЛФ) [31].…”
unclassified